The Implementation of SMART-Q in Enhancing Islamic Values in Islamic Junior High School Education - Umi Maysaroh; Elok Rufaiqoh; Zainal Arifin (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of SMART-Q, or Spiritual Morality and Reflective Tahfidz Qur’an, and its role in strengthening Islamic values among junior high school students. This research used a descriptive qualitative method involving the principal, teachers, and students as informants. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. Source and technique triangulation were used to ensure data validity. The findings show that SMART-Q was implemented systematically through the 3T 1M method, consisting of taqrir, tafahum, tasmi’, and murojaah. The program was also supported by Qur’an memorization submission and murojaah kubro activities. SMART-Q had a positive impact on students’ religious behavior, especially in improving morality, worship consistency, discipline, and self-control. The study implies that integrating Qur’an memorization, moral guidance, and self-reflection can serve as an effective strategy for developing students’ Islamic character in secondary education.